Changes in the geographical distribution of global iron ore shipping flows, 2000–2019. (February 2022) - Zhao, Pengjun; He, Zhangyuan; Yin, Liangming; Xiao, Renrong; Chen, Jun; Tang, Junqing; Gong, Zhao Ya; Zhang, Wenjia
Highlights: The geographical distribution of iron ore trade shipping flows has radically changed in 2000–2019. The emerging industrializing countries have become the main importers of iron ore. The shipping routes from Australia-Asia, Brazil-Asia, and South Africa-Asia are facing heavier demand. A few countries dominate the iron ore supply that will not change in the near future. The global geopolitical situation is becoming more uncertain, which may challenge industrialization in emerging economies.